ChemInform Abstract: [3]Dendralene Synthesis: Rhodium(III)‐Catalyzed Alkenyl C—H Activation and Coupling Reaction with Allenyl Carbinol Carbonate. Issue 16 (22nd April 2014) - Wang, Honggen; Beiring, Bernhard; Yu, Da‐Gang; Collins, Karl D.; Glorius, Frank
Abstract This method gives access to a variety of [3]dendralenes with diverse substitution patterns and diene‐substituted arenes.